2022
DOI: 10.5194/hess-26-4801-2022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a national 7-day ensemble streamflow forecasting service for Australia

Abstract: Abstract. Reliable streamflow forecasts with associated uncertainty estimates are essential to manage and make better use of Australia's scarce surface water resources. Here we present the development of an operational 7 d ensemble streamflow forecasting service for Australia to meet the growing needs of users, primarily water and river managers, for probabilistic forecasts to support their decision making. We test the modelling methodology for 100 catchments to learn the characteristics of different rainfall … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 64 publications
6
34
1
Order By: Relevance
“…Ensemble forecasting is considered more reliable and skilful, and it can greatly benefit water resource management by providing useful information about uncertainty [7]. In response to customer needs, the Bureau progressively developed the 7-day ensemble streamflow forecasting, and released it to the public in 2020 [8]. This is a comprehensive, nation-wide service for Australia, and covers most water resources catchments of high economic value and social significance [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ensemble forecasting is considered more reliable and skilful, and it can greatly benefit water resource management by providing useful information about uncertainty [7]. In response to customer needs, the Bureau progressively developed the 7-day ensemble streamflow forecasting, and released it to the public in 2020 [8]. This is a comprehensive, nation-wide service for Australia, and covers most water resources catchments of high economic value and social significance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Australia has a wide range of climate zones as defined by Köppen Climate Classification [10] -including tropical region in the north, temperate regions in the south, grassland and desert in the vast interior. Annual rainfall for each of the divisions vary from a 410 to 2800 mm [8]. The distribution of annual rainfall and Potential evapotranspiration (PET) varies significantly across the continent (http://www.bom.gov.au/jsp/ncc/climate_averages/rainfall/index.jsp, accessed 11 November 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable and skillful streamflow forecasts are crucial for informing decisions related to water resources management, water supply planning, and preparedness against extreme events. The ensemble prediction system is becoming increasingly popular for streamflow forecasting (Cloke & Pappenberger 2009;Demargne et al 2014;Troin et al 2021;Hapuarachchi et al 2022;Liu et al 2022), as they have demonstrated substantial improvements over the single-valued deterministic forecasts (Siddique & Mejia 2017). An ensemble prediction system can provide multiple realizations of possible streamflow conditions enabling decision-makers to have a better idea of the likelihood of a specific future event (e.g., the probability of exceeding a flood threshold).…”
Section: Introductionmentioning
confidence: 99%
“…Within an ensemble prediction system, hydrological models are generally forced with ensemble meteorological forecasts from weather prediction models (Demargne et al 2014;Pagano et al 2016;Alfieri et al 2017;Siddique & Mejia 2017;Zhang et al 2020;Hapuarachchi et al 2022;National Weather Service 2022) as opposed to streamflow simulations, which are often generated by hydrological models forced with meteorological observations (Kratzert et al 2018;Feng et al 2020;Konapala et al 2020). In the United States, the NOAA's National Weather Service River Forecast Centers are implementing the Hydrological Ensemble Forecast Service (HEFS) to incorporate meteorological ensembles into their flood forecasting operations (Brown et al 2014;Kim et al 2018;National Weather Service 2022).…”
Section: Introductionmentioning
confidence: 99%